Sosialisasi dan Pelatihan Pemanfaatan Limbah Kulit Kopi menjadi Teh Herbal Cascara Celup - Naufali, Muhammad Nizhar; Ni Wayan Putu Meikapasa; Dwi Aulia Savitri (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
Cascara are side material that resulting from grinding the coffee beans. Cascara can be processed into refreshing herbal tea contain high nutrition level and it has profitable economic value. Women Farmers group (KWT) Elong Tuna located in Lantan Village, North Batukliang District Central Lombok Regency are only considered that cascara is just a waste material and not utilized to lack of knowledge and information about how to processed it. This community service activity (PkM) was aim to give education and information about benefits of cascara as well as providing training on how to process cascara into herbal tea. The method used in this Community Service Program (PkM) is socialization with presentations, discussions and training on how to processing cascara into cascara herbal tea. The community members of the Women's Farmers Group (KWT) Elong Tuna feel that from this Community Service Program (PkM) they have gained knowledge in processing cascara and are motivated to produce cascara herbal tea in order to increase income for the KWT members.